Erthesina fullo (Hemiptera: Heteroptera: Pentatomidae): old and new stories of an invasive stink bug - Kment, Petr; Lavay, Martin; Zeman, Šimon; Yasunaga, Tomohide (Zootaxa, 2023)
The Yellow-Spotted Stink Bug Erthesina fullo (Thunberg, 1783) (Pentatomomorpha: Pentatomoidea: Pentatomidae: Pentatominae: Halyini), native in East and South-East Asia, was recently discovered introduced in both Europe (Albania, 2017) and South America (Brazil: São Paulo, 2020). We report two cases of interception of living specimens in the Czech Republic. The first specimen (Zlín, 2021) was found in a sealed container with shoes imported from China, the second specimen (Prague, 2023) was recieved in a parcel sent from Poland. We also present the interesting story of Erthesina fullo in Japan, where the species was introduced to Dejima Island in Nagasaki (Kyushu) already before 1775; at that time Dejima was the only place in Japan where Dutch and Chinese ships were allowed to trade during the isolationist Edo period (1603–1868). One old name, also proposed based on specimens originating from Japan, Cimex aloes Lichtenstein, 1796, syn. nov., is proposed a junior subjective synonym of E. fullo. The invasion of Erthesina fullo in Japan seems to be the oldest exactly localised invasion in Heteroptera. The taxonomy of Erthesina Spinola, 1837 is discussed, the genus currently includes 9 species. The genus is in urgent need of revision and the resulting problems with identification of its species, including E. fullo, are pointed out. Distribution of all Erthesina species is briefly reviewed.